2023
DOI: 10.1200/jco.22.00980
|View full text |Cite
|
Sign up to set email alerts
|

Results of Phase III Randomized Trial for Use of Docetaxel as a Radiosensitizer in Patients With Head and Neck Cancer, Unsuitable for Cisplatin-Based Chemoradiation

Abstract: PURPOSE There is a lack of published literature on systemic therapeutic options in cisplatin-ineligible patients with locally advanced head and neck squamous cell carcinoma (LAHNSCC) undergoing chemoradiation. Docetaxel was assessed as a radiosensitizer in this situation. METHODS This was a randomized phase II/III study. Adult patients (age ≥ 18 years) with LAHNSCC planned for chemoradiation and an Eastern Cooperative Oncology Group performance status of 0-2 and who were cisplatin-ineligible were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Recently, Patil et al evaluated the use of docetaxel as a radiosensitizer in patients with advanced head and neck cancer who could not receive cisplatin. They found that concurrent docetaxel showed promising results as a treatment option for cisplatin-ineligible patients with advanced head and neck cancer treated with radiotherapy [ 25 ]. A rigorous review by a multidisciplinary specialist treatment team is required when deciding on a treatment plan for LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Patil et al evaluated the use of docetaxel as a radiosensitizer in patients with advanced head and neck cancer who could not receive cisplatin. They found that concurrent docetaxel showed promising results as a treatment option for cisplatin-ineligible patients with advanced head and neck cancer treated with radiotherapy [ 25 ]. A rigorous review by a multidisciplinary specialist treatment team is required when deciding on a treatment plan for LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies that indicate that nivolumab may be dosed lower than proposed by use here [39,40], yet results are conflicting and higher doses of nivolumab appear to be required for the treatment of lung cancer [41][42][43]. Although we specifically focused on monoclonal antibodies and antibody-drug conjugates used for the treatment of lung cancer, most drugs in our analysis have broader indications.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, several cytotoxic anti-cancer agents, such as taxane-based anticancer drugs, such as docetaxel and paclitaxel, were more conventionally used for HNSCC [ 1 ]. Combined treatment of docetaxel and cisplatin for advanced HNSCC showed a good response of 33–53% [ 48 ]. Based on the above data, we employed the pRRophetic algorithm to study the impact of the risk model on the response of four common anti-cancer agents, such as cisplatin, paclitaxel, gemcitabine, and docetaxel.…”
Section: Discussionmentioning
confidence: 99%